Exploring Project-Based Learning in the SVVR Environment: An Epistemic Network Analysis of Pre-service EFL Teachers - Darmawansah; Puspitasari, Dani (Script Journal: Journal of Linguistics and English Teaching, 2024)
Background:The goal is to explore how pre-service EFL teachers develop spherical video virtual reality (SVVR) projects, applying technological (TK), pedagogical (PK), and content knowledge (CK). Methodology: The data was collected from artifacts of pre-service EFL teachers' SVVR, and then analyzed using epistemic network analysis, a quantitative ethnography analysis. Findings: The pre-service EFL teachers primarily utilized TK features when designing virtual reality projects. These projects incorporated text-to-speech (TTS) to offer authentic speakers. Conclusion: This study showcased the extent to which pre-service EFL teachers developed their virtual reality projects and the features they used. Originality: Our study, utilizing epistemic network analysis, adds a layer to the common analysis, enriching the understanding of pre-service teachers' SVVR projects.